A hypothermia-sensitive micelle with controlled release of hydrogen sulfide for protection against anoxia/reoxygenation-induced cardiomyocyte injury. (15th July 2022) - Wen, Lianlei; Yan, Tao; Xiao, Yan; Xia, Wenyi; Li, Xueyan; Guo, Changfa; Lang, Meidong
Graphical abstract: Highlights: The micelle exhibited reversible LCST-forming thermo-sensitivity with low cloud point ( T cp ) of 13 °C. With the disassembly of micelle at 4 °C, hypothermia-sensitive micelle enjoyed a continuous release profile of H2 S under the thiol-trigger condition. Compared with traditional H2 S donors of sodium hydrosulfide (NaHS) and thiobenzamide, the incorporation of H2 S donor into micelle displayed excellent biocompatibility for cardiomyocytes, even at a high concentration. Released H2 S from micelles could provide a significant protection for cardiomyocytes against anoxia/reoxygenation(A/R)-induced injury. Abstract: Hydrogen sulfide (H2 S) provided a potential strategy to protect heart from ischemia-reperfusion injury (IRI). However, controllable and continuous H2 S level for long periods of time remained challengeable in the aspect of maintaining viability of heart in cold storage. Hence, we investigated the protective efficiency of hypothermia-sensitive micelle with controlled release of H2 S for cardiomyocyte through in vitro anoxia/reoxygenation (A/R) cardiomyocyte models. This micelle was fabricated through the self-assembly of an amphiphilic deblock copolymer methoxy poly(ethylene glycol)-poly( N -pyrrolidine-formyl-caprolactone- co -thiobenzamide-caprolactone) (mPEG-P(VPyCL- co -TBA-CL)). Benefiting from the reversible lower critical solution temperature (LCST)-type behavior with low cloud point ( T cp ) of 13 °C, self-assembled micelle could control the release of H2 S in response to temperature under the thiol-triggered condition. Noteworthily, with the disassembly of micelle at 4 °C, micelles enjoyed a controllable and continuous release profile of H2 S. By mimicking the cold storage of the heart against IRI, released H2 S from micelle was demonstrated to provide a significant protection for cardiomyocytes against A/R-induced injury. Taken together, we envisioned that this work offered a potential hypothermia-sensitive material with controlled release of H2 S promising for heart preservation against IRI in cold storage.